Kako učitelji kemije udejanjajo svoje potrebe profesionalnega razvoja v sistemu nadaljnjega izobraževanja in usposabljanja - Sikošek, Darinka; Čagran, Branka (Revija za elementarno izobraževanje, 2016)
How Slovenian Chemistry Teachers Meet their Needs for Professional Development in the System of Further Education and Training. The primary purpose of further education and training, as a form of lifelong learning, is to provide professional development and professional and personality growth of different professional profiles, including teachers. The type and quality of programmes intended for further education and training of professionals in education and training, especially of chemistry teachers, precisely is the central theme of this contribution. Based on the results of an empirical research carried out on a sample of chemistry teachers in Slovenian basic and secondary schools during the 2009/10 school year, we find that the desire to develop skills is the main motive power (Lat. nervus rerum) of their participation in the programmes published in the Catalogue of Further Education and Training (FET) Programmes, and inadequate time of implementation of programmes—regarding teachers’ teaching duties— the fundamental obstacle. The most frequently teachers of course attend modernisation programmes, followed by programmes not published in the Catalogue.
Keywords: further education and training of the teachers; the competences of lifelong learning; Catalogue of programmes for further education and training of professionals in education and training; chemistry teachers